Race in the Bahamas: A Dysfunctional Narrative - Russell, Keith Alton (International Journal of Bahamian Studies, 2009)
This essay addresses the ways in which the conversation about race in The Bahamas is predicated upon avoidance, obfuscation, and incoherence. Further, it critiques some traditional and sacred narratives concerning the protracted problems of race in the Bahamian archipelago. Then, briefly, it examines the historical circumstances which gave rise to the present paralysis, and offers suggestions on how to move forward towards “one Bahamas”, thus overcoming the obvious racial divide, and simultaneously, healing some old wounds too long left to fester.